Exploring market challenges and entrepreneurial opportunities in plus-size women’s fashion in Malaysia - Haslin, Nur Syafiqah Suhaili; Ahmad, Hasma (Faculty of Business and Management, 2025)
This study investigates the challenges faced by plus-size women in Malaysia’s ready-to-wear fashion industry, with a focus on issues of fit, accessibility, affordability and representation. Using a qualitative approach, insights were gathered from 34 Malaysian women aged 18 to 50 through open-ended survey responses. The findings highlight structural market gaps, including inconsistent sizing and poor fit, limited retail availability, design and aesthetic shortcomings, premium pricing, negative consumer experiences, and a lack of inclusive marketing strategies. These barriers reveal untapped opportunities for businesses and entrepreneurs to address underserved consumer needs through innovation, customer-centred product development, and inclusive marketing approaches. Beyond contributing to social inclusion, such strategies hold significant potential to enhance competitiveness and stimulate growth in Malaysia’s fashion sector, with broader implications for emerging markets seeking to strengthen consumer engagement and expand into niche yet high-potential segments.